Gender Role Attitudes: An Examination of Cohort Effects in Japan. Issue 4 (29th April 2019) - Piotrowski, Martin; Yoshida, Akiko; Johnson, Lauren; Wolford, Rick
Abstract : Objective: This study examines cohort differences in attitudes toward women's roles within marriage in Japan. Background: Japan has undergone dramatic sociocultural shifts in the 20th century that have shaped childhood experiences differently by cohort. Sociodemographic perspectives predict cohort effects, which suggest the lasting impact of experiences during the formative years on attitudes. Method: This study employs a hierarchical age‐period‐cohort analysis and uses repeated cross‐sectional data from the 2000 to 2012 Japanese General Social Survey ( N  = 31, 912), a nationwide probability survey. Results: Among cohorts born before 1960, for both sexes, attitudes toward wife's employment and a gender‐based division of labor were significantly less traditional for later born cohorts. However, younger cohorts born in 1960 and after were not significantly different in their attitudes from the cohort born in the 1950s. Conclusion: This study suggests the strong impact of ideological shifts and mothers' homemaking role (experienced in one's formative years) on gender role attitudes. It points to the important and lasting influence of structural contexts on attitudes and hence cohort effects. Implications: This study contributes to our understanding of attitudinal change (and stagnation) toward gender roles and has policy implications for Japan and other countries characterized by low marriage and fertility rates.